Territory, Religion and Conflict of Identities. (Revista LIDER, 2018)
The article analyzes identity from the concepts of religion and territory in San Felipe Teotitlán, Estado de México, for religious practices and territory limits, constructed symbolic borders that transcend the conflict of identities and determines social relationships among individuals belonging to different neighborhoods that make up the community. Religious elements correspond to the objectification of a religious figure: El Divino Rostro, as a patron saint, and his apprehension -or not- for the subject impacts its definition over the other; territorially, it converges with religious beliefs and practices in the imputed and internalized identity.